Ethnomathematical Values in Sitiwinangun Traditional Pottery and Its Potential for Contextual Mathematics Learning - Zalfaanisa Maryani; Sansan Nurhasanah; Miqdad Dhiya Ulhaq; Arif Muchyidin (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study examines ethnomathematical values embedded in traditional pottery crafts in Sitiwinangun Village, Cirebon Regency, Indonesia, and discusses their potential for contextual mathematics learning. Using an exploratory qualitative case-study design, data were collected through non-participant observation, semi-structured interviews with craftsmen, and visual documentation. The analysis reveals mathematical ideas in both the pottery forms and production process, including spatial geometry (circles, cylinders, cones, and spheres), radial symmetry, proportional reasoning, rotation, and volume estimation. Traditional tools such as the spinning wheel (petra) illustrate rotational principles that can support learning in geometry and related mathematical concepts. Beyond mathematical aspects, pottery artefacts (e.g., jugs) also convey cultural-symbolic values associated with balance in local traditions. Digital visualisation of pottery shapes using Maple software further supports geometric understanding. To our knowledge, the ethnomathematical exploration of Sitiwinangun pottery as a contextual learning resource has received limited attention. These findings indicate that pottery-based ethnomathematics can enrich geometry instruction by connecting cultural practices with formal mathematical concepts and informing the development of local culture-based learning modules.